A hopeful study of hop - Mackegård, Ida Elisabeth (2021)
Historically cultivated grown hop usually have an early maturation, this is important for developing α and β – acid. In addition, these varieties often come with an interesting history and have the potential to give the local beer an even more local connection. The objective of this study was to investigate the agronomic-quality of historically cultivated Swedish hop varieties in the search for an early maturing high α - acid-producing hop variety, that could give both good yield and good quality. 11 hop varieties were grown in a field in Krusenberg outside Uppsala, ten Swedish varieties and one variety from the Czech Republic. The trial was investigated by going out to the field trial once a week during the growing season to note development stages. Mean of development time between the varieties was compared. Overall plant health was also noted but not quantified. Hops were harvested when they reached assumed maturation, based on smell, and looks of cones. The cones were dried in 60 °C in 2-3 hours until they reached 10 % moisture. Analysis of α and β – acid content was performed along with total essential oil, and proportion of myrcene α-humulene, β-caryophyllene, farnesene, linalool, limonene, and geraniol. The study conclude that Korsta is the variety that seems most interesting as it has the highest yield, alpha acid, and essential oil. As the variety has high myrcene values it might be suitable for brewing fruitier ales or IPA. Hulla Norrgård is another interesting variety with early maturation, big cones, and a high α – acid. Hulla norrgård is also high myrcene containing variety, indicating that it would be suitable for fruitier ales or IPA. Bonneråd was amongst the lower α – acid varieties but had a high total essential oil content. This variety could be interesting for lager beers as it has low myrcene and moderate levels of α-humulene, β-caryophyllene, and farnesene. Tvärud is another variety with moderate levels of α-humulene, and myrcene an could be suitable for lager style beers.